Selenium-enriched plant foods: Selenium accumulation, speciation, and health functionality - Tangjaidee, Pipat; Swedlund, Peter; Xiang, Jiqian; Yin, Hongqing; Quek, Siew Young (Frontiers in Nutrition, 2023)
Selenium (Se) is an essential element for human health functions. Se compounds' biological effects and toxicity on human health are related to their chemical forms and consumption doses. In general, organic Se species, including selenoamino acids such as selenomethionine (SeMet), selenocystine (SeCys2), and Se-methylselenocysteine (MSC), could provide greater bioactivities with less toxicity compared to those inorganics including selenite (Se IV) and selenate (Se VI). Plants are vital sources of organic Se because they can accumulate inorganic Se or metabolites and store them as organic Se forms. Therefore, Se-enriched plants could be applied as human food to reduce deficiency problems and deliver health benefits. This review describes the recent studies on the enrichment of Se-containing plants, their functional properties related to human health, and future perspectives for developing Se-enriched foods. Generally, Se's concentration and chemical forms in plants are determined by the accumulation ability of plant species. Brassica family and cereal grains have excessive accumulation capacity and store major organic Se compounds in their cells compared to other plants. Functionalities of Se-enriched plants, including antioxidant, anti-diabetes and anticancer properties, have significantly presented in both in vitro cell culture models and in vivo animal assays. Comparatively, fewer human clinical trials are available. Scientific investigations on the functional properties of Se-enriched edible plants in humans are essential to achieve in-depth information supporting the value of Se-enriched food to humans.